Correlations between conductivity, electroluminescence and flash sintering. (June 2016) - Naik, K.; Jha, S.K.; Raj, R.
Abstract: Flash experiments with single phase SrTiO3, and two-phase composites of SrTiO3 containing 2.5–20 vol% of KNbO3, reveal remarkably different outcomes. While all compositions show the classical signature of the flash, that is, a sudden increase in conductivity, and electroluminescence, only the pure SrTiO3 specimen sinters fully. The composites show only some densification. The results are interpreted in terms of the nature of the interphase grain boundaries, which are expected to be "metallic". They further lead to an understanding of whether flash sintering originates primarily at grain boundaries or within the grain matrix. Graphical abstract: Remarkable effect of very small volume fractions of potassium niobate, KN, on flash sintering of strontium titanate, ST.